Characteristics and outcomes of patients hospitalised with acute heart failure at a tertiary hospital in South Africa - Mazaza, A; Weich, H; Doubell, AF (SA Heart Journal, 2026)
Aims: Acute heart failure (AHF) remains a major public health challenge in sub-Saharan Africa, yet contemporary data on its clinical characteristics and management outcomes are limited. This study aims to characterise the epidemiology, treatment patterns, and clinical outcomes of AHF patients in a South African tertiary care setting in the era of modern heart failure (HF) therapy. Methods: We conducted a retrospective study of 339 AHF admissions at Tygerberg Hospital (TBH), Cape Town, during 2022. Comprehensive data, including demographics, clinical characteristics, investigations (echocardiography, coronary angiography), treatment regimens, and outcomes, were analysed. Patients were identified using the International Classification of Diseases, Tenth Revision (ICD-10) codes for HF and cardiomyopathy. Results: The cohort (mean age 53 ± 15.4 years, 51.9% male) demonstrated a high burden of non-ischaemic cardiomyopathy with HF with reduced ejection fraction (HFrEF) predominance (91%). Comorbidities were highly prevalent (74% hypertension, 43.4% diabetes). While conventional guideline-directed medical therapy (GDMT) utilisation was robust (88.7% beta blocker [BB], 87.5% angiotensin-converting enzyme inhibitor [ACEi]/ angiotensin receptor blocker [ARB]), novel therapies were markedly underutilised (3.9% sodium-glucose cotransporter 2 inhibitor [SGLT2i], 1.3% angiotensin receptor-neprilysin inhibitor [ARNi]). Only 42.9% of eligible patients for cardiac resynchronisation therapy (CRT) received implants. Clinical outcomes included rates of 3.9% in-hospital mortality, 27.7% 2-year case fatality, and 44.3% 30-day re-admission. Conclusions: This study reveals a distinct AHF phenotype in South Africa, characterised by younger patients with a predominant non-ischaemic aetiology and high comorbidity burden. Despite adequate conventional GDMT implementation, significant therapeutic gaps persist in advanced therapies. The substantial re-admission burden highlights critical health system challenges, emphasising the urgent need for healthcare policy reforms and optimised care pathways in resource-limited settings.